A multifunctional triazine-based nanoporous polymer as a versatile organocatalyst for CO2 utilization and C–C bond formation. Issue 77 (9th September 2019) - Sharma, Ruchi; Bansal, Ankushi; Ramachandran, C. N.; Mohanty, Paritosh
Abstract : Conversion of CO2 to cyclic carbonates, methanol and methane by using a nanoporous MNENP as a multifunctional metal-free organocatalyst. Abstract : A triazine-based nanoporous multifunctional polymer with a SABET of 304 m 2 g −1 has shown versatile catalytic activity in the conversion of CO2 to cyclic carbonates at 4 bar with almost 100% yield and selectivity, and in the conversion of CO2 to methanol and methane electrochemically. Additionally, it also catalyzes C–C bond formation via the Knoevenagel reaction.